Developing a language screening scale that considers linguistic diversity in pre-school children - Kanikli, Antri; Spanoudis, George Charilaos; Theodorou, Elena (Frontiers in Communication, 2025)
This paper presents an extensive analysis of the techniques adopted in the creation of a new language assessment instrument, the Screening Scale of Language Development (SSLD). Standardized in Cyprus, the SSLD aims to identify language deviations in children before they enter primary school. The initiative addresses a significant gap in assessment tools that consider the linguistic diversity present in Cyprus. The scale items were developed based on recent studies focusing on clinical indicators and prognostic factors of developmental language disorders. This approach ensured that the items effectively represent the language varieties utilized by Greek Cypriot preschool children. The findings of the psychometric evaluation of the SSLD strongly endorse its structural validity. The evaluation demonstrates the SSLD's reliability as an instrument for assessing language growth in Greek Cypriot children. The SSLD initiative not only provides a robust tool backed by strong psychometric foundations, but also empowers professionals to confidently detect language difficulties in a diverse linguistic context. This research underscores the importance of culturally and linguistically relevant assessment tools in early childhood education.